Three rare and accidental findings of hemoglobinopathies encountered in high-performance liquid chromatography: case series - Trivedi, Dhara P.; Joshi, Hetal A.; Popat, Vijay C. (International Journal of Research in Medical Sciences, 2022)
Hemoglobinopathies are the leading cause of some major genetic and social health problem in India. Among all hemoglobinopathies, sickle cell disorder and thalassemia are commonly found in Gujarat state. Double heterozygous state of hemoglobin S and D, hemoglobin E trait, hemoglobin D disease are very uncommon. In present instance, one case of 25-year-old male was diagnosed with sickle cell hemoglobin D disease. The case was confirmed through slide-based sickle test and high-performance liquid chromatography (HPLC). The peripheral smear findings showed presence of microcytic hypochromic red blood cells (RBCs) and many sickled RBCs. Ultrasonography (USG) findings showed hepatomegaly. Second case of 30-year-old female was diagnosed with hemoglobin E trait. The case was confirmed by HPLC. The peripheral findings showed normocytic normochromic RBCs and occasional target cells. Presence of gross hepatomegaly on palpation. Third case of 20-year-old female was diagnosed with hemoglobin D trait. The case was confirmed by HPLC. The peripheral findings showed normocytic normochromic RBCs.